Antimicrobial activity of natural dyes obtained from Pterocarpus indicus Willd barks - Saivaraj, S; Chandramohan, G. (Asian Journal of Pharmaceutical Research and Development, 2018)
In the present study to evaluate the antimicrobial activity of Pterocarpus indicus barks. Many of the plant materials, from which natural dyes are obtained, found to have some medicinal values. During the present study, dying materials were prepared from barks of Pterocarpus indicus. The well diffusion method was adopted to examine antimicrobial activity of dying material against test organisms. The result showed that thedying material of Pterocarpus indicus was most active for antibacterial(9 mm) and antifungal (6 mm).Results of the present study suggest that the dying material of Pterocarpus indicus has signiﬁcant antibacterial activity against pathogenic bacteria and fungus. Key words: